PostGIS cookbook : over 80 task-based recipes to store, organize, manipulate, and analyze spatial data in a PostGIS database /: over 80 task-based recipes to store, organize, manipulate, and analyze spatial data in a PostGIS database. (2014) - Unknown
No abstract available